Drosophila melanogaster as a Biotechnological Tool to Investigate the Close Connection Between Fatty Diseases and Pesticides - de Oliveira-Júnior, Fabiano Cláudio [UNESP]; de Oliveira, Ana Caroline Pimentel [UNESP]; Pansa, Camila Cristiane [UNESP]; Molica, Letícia Ramos [UNESP]; Moraes, Karen C.M. [UNESP] (FapUNIFESP (SciELO), 2024)
Nonalcoholic fatty liver disease (NAFLD) is a public health problem developed by different etiologies, which induces metabolic dysfunctions and triglycerides accumulation in hepatocytes. This lipid accumulation can generate lipotoxicity, inflammation and the production of reactive oxygen species, collaborating with the progression of liver pathogenesis to more deleterious stage. Among the elements that initiate the establishment of liver diseases, pesticides should be considered. Worldwide, the use of agricultural chemicals to increase food production may accumulate in the environment, affecting non-target organisms. Thus, worldwide legislation must control pesticides use to preserve economies and lives. In this context, to address pesticide toxicity, the alternative animal model, Drosophila melanogaster, emerges as relevant biotechnological tool to investigate molecular connectors of toxic mechanisms in the establishment and development of NAFLD and liver diseases. In this review a comprehensive explanation about pesticides on human health and the use of Drosophila melanogaster as an alternative approach to defeat NAFLD will be presented.(Figure presented)
Keywords: alternative animal model; biotechnology tools; NAFLD; pesticide; public health